A high-strength nano-alumina ceramic product and its preparation process

By forming a polydopamine layer on the surface of the silicon carbide whiskers and embedded in the silicon gel network structure, combined with the use of composite adhesives, the problem of uneven structure of alumina ceramics and prone to agglomeration of silicon carbide whiskers during high-temperature sintering is solved, and the mechanical strength and density of nano-alumina ceramics are significantly improved.

CN119390466BActive Publication Date: 2025-04-11YIXING MINGHAOTE CERAMIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411610865.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-04-11
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Alumina ceramics are prone to growth anisotropy and abnormal grains during high-temperature sintering, resulting in uneven structure and silicon carbide whiskers are prone to agglomeration, affecting the mechanical strength of nano-alumina ceramics.

Method used

By forming a polydopamine layer on the surface of the silicon carbide whiskers, adsorbing zirconium oxychloride and magnesium nitrate hexahydrate, forming modified silicon carbide whiskers and embedding them into the silicon gel network structure, combined with composite adhesives to improve the density and mechanical strength of the nano-alumina ceramics.

Benefits of technology

The mechanical strength and density of nano-alumina ceramics are significantly improved, the porosity increases caused by the agglomeration of silicon carbide whiskers, and the stability and thermal stability of the ceramics are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of nano ceramic materials, and discloses a high-strength nano alumina ceramic product and a preparation process thereof, comprising the following preparation steps: mixing alumina powder, a composite binder, a composite gel, a plasticizer, and a solvent, ball milling, and obtaining a composite slurry; placing the composite slurry in a mold, performing mold pressing and drying, and obtaining a green body; placing the green body in a high-temperature sintering furnace, performing high-temperature sintering, and cooling to room temperature to obtain a nano alumina ceramic product. Nano zirconium oxide and nano magnesium oxide are formed on the surface of pre-treated silicon carbide whiskers, and during the sintering process, they can form a solid solution with nano alumina as a bridge between silicon carbide whiskers and nano alumina particles, significantly enhancing the bonding force of silicon carbide whiskers in a nano alumina ceramic matrix; phosphoric acid and ammonium aluminum sulfate are firmly bonded to the surface of nano alumina particles through carboxymethyl cellulose, avoiding weak bonding between phosphoric acid and ammonium aluminum sulfate and nano alumina particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano ceramic materials, in particular to a high-strength nano alumina ceramic product and a preparation process thereof. Background Art

[0002] Alumina ceramic materials mainly include structural ceramics and functional ceramics. They are a type of polycrystalline solid material, usually formed after high-temperature sintering. Alumina ceramic materials are widely used in electronic chemical industry, new energy, aerospace, machinery manufacturing and other fields due to their own excellent properties, such as high stability, high temperature resistance, high hardness, strong acid and alkali corrosion resistance, and very low dielectric loss. Nano-alumina particles have obvious surface effect and small size effect, which can increase the surface energy of oxide ceramic particles, enhance the activity during sintering, significantly reduce the sintering temperature, and improve the densification of the green body, so that the microstructure of the obtained ceramic material and the size distribution of the grains are more uniform, and the toughness, strength and plasticity of the material are greatly improved, and alumina ceramic materials with excellent mechanical properties can be obtained.

[0003] Alumina ceramics are prone to growth anisotropy and abnormal grains during high-temperature sintering, resulting in uneven structure and even residual pores inside, which reduces the bonding strength between the grains, causing a significant decline in material properties and limiting the application and development of alumina ceramics. The use of silicon carbide whiskers to toughen nano-alumina ceramics can significantly improve the toughness and mechanical strength of nano-alumina ceramics, but during the sintering process of nano-alumina ceramics, silicon carbide whiskers are prone to agglomeration, resulting in a decrease in the density of nano-alumina ceramics, affecting the mechanical strength of nano-alumina ceramics. Summary of the invention

[0004] The invention provides a high-strength nano-alumina ceramic product and a preparation process thereof, which solves the problems of growth anisotropy and abnormal grains and easy agglomeration of silicon carbide whiskers in the process of high-temperature sintering of alumina ceramics.

[0005] The technical solution of the present invention:

[0006] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0007] S1. The alumina powder, composite binder, composite gel, plasticizer, and solvent were mixed and ball-milled for 20-22h to obtain a composite slurry;

[0008] S2. The composite slurry is placed in a mold, molded and dried to obtain a green body;

[0009] S3. The green body is placed in a high temperature sintering furnace, sintered at high temperature, and then cooled to room temperature to obtain a nano-alumina ceramic product;

[0010] The composite gel is obtained by mixing and reacting modified silicon carbide whiskers, a crosslinking agent and a silicon precursor;

[0011] The modified silicon carbide whisker is obtained by mixing pretreated silicon carbide whisker, zirconium oxychloride and magnesium nitrate hexahydrate and calcining at high temperature;

[0012] The composite binder is obtained by mixing a phosphoric acid aqueous solution, an ammonium aluminum sulfate aqueous solution and carboxymethyl cellulose.

[0013] Furthermore, the alumina powder is selected from α-alumina, with a content of 99.5-99.8% and a particle size of 100-300nm.

[0014] Furthermore, the plasticizer is selected from polyethylene glycol.

[0015] Furthermore, the solvent is selected from ethanol.

[0016] Furthermore, the mold size (length, width, height) is 40 mm×40 mm×50 mm.

[0017] Furthermore, the molding drying pressure is 80-100 MPa, the molding drying temperature is 70-90° C., and the molding drying time is 25-35 min.

[0018] Furthermore, the high temperature sintering process: heat up to 480-520°C at a heating rate of 1-3°C / min, and keep warm for 28-32min; then continue to heat up to 980-1020°C at a heating rate of 2-4°C / min, keep warm for 28-32min, and finally heat up to 1480-1550°C at a heating rate of 4-6°C / min, and keep warm for 2-4h.

[0019] Furthermore, the mass ratio of alumina powder, composite binder, composite gel, plasticizer and solvent is (90-100):(8-10):(10-12):(1-3):(25-35).

[0020] Furthermore, the composite gel is specifically prepared by the following steps:

[0021] A1. Add silicon carbide whiskers to a Tris-HCl buffer having a pH of 8-9, stir evenly, add dopamine, stir the reaction, filter, wash, and dry to obtain pretreated silicon carbide whiskers;

[0022] A2. The pretreated silicon carbide whiskers, zirconium oxychloride, and magnesium nitrate hexahydrate were added to deionized water, stirred evenly, and ammonia water with a concentration of 4-6 mol / L was added to adjust the pH to 8-9, stirred at a rate of 350-450 rpm for 25-35 min, filtered, dried, placed in a muffle furnace, calcined at 1200-1300 ° C for 20-23 min, and cooled to room temperature to obtain modified silicon carbide whiskers;

[0023] A3. Mix the modified silicon carbide whiskers with 1-3% by mass of a cross-linking agent, stir at a rate of 450-550 r / min for 1-3 hours, add a silicon precursor and ethanol, stir until gelation, take out the gel, and wash it to obtain a composite gel.

[0024] Furthermore, during the above-mentioned A1 reaction, the phenolic hydroxyl structure contained in dopamine has good adhesion, and dopamine can self-polymerize in Tris-HCl buffer to form a polydopamine layer on the surface of the silicon carbide whisker, thereby giving the silicon carbide whisker excellent adhesion.

[0025] Furthermore, during the above-mentioned A2 reaction process, the polydopamine layer contained on the surface of the pretreated silicon carbide whisker has good adhesion and can adsorb zirconium oxychloride and magnesium nitrate hexahydrate onto the surface of the pretreated silicon carbide whisker. Ammonia water, as a precipitant, can combine with zirconium and magnesium ions in zirconium oxychloride and magnesium nitrate hexahydrate to form hydroxides. Further, sintering is carried out at 1250°C for 20 minutes, and the hydroxide precipitates and pyrolyzes to form zirconium oxide and magnesium oxide, thereby forming nano zirconium oxide and nano magnesium oxide on the surface of the pretreated silicon carbide whisker.

[0026] Furthermore, during the above-mentioned A3 reaction process, the modified silicon carbide whiskers are mixed with a crosslinking agent chitosan solution to form a gel precursor. The chitosan solution has a high viscosity to maintain the dispersion stability of the modified silicon carbide whiskers, and the silanol groups formed by the hydrolysis of the silicon precursor can undergo a cross-linking reaction with chitosan to form a gel structure of a cross-linked network, so that the modified silicon carbide whiskers are embedded in the silicone gel network structure, thereby achieving fixation of the modified silicon carbide whiskers by the composite gel.

[0027] Furthermore, in step A1, the ratio of the silicon carbide whisker, Tris-HCl buffer, and dopamine is (2-2.5) g: (45-50) mL: (0.6-1) g.

[0028] Furthermore, in step A2, the ratio of the pretreated silicon carbide whisker, zirconium oxychloride, magnesium nitrate hexahydrate, and deionized water is (5-6) g: (1-2) g: (1.2-1.4) g: (45-55) mL.

[0029] Furthermore, in step A3, the amount ratio of the modified silicon carbide whisker, the crosslinking agent, the silicon precursor, and the ethanol is (1-2) g: (15-25) mL: (0.3-0.7) g: (8-12) mL.

[0030] Furthermore, the diameter of the silicon carbide whisker is 80-100 nm and the length is 0.2-1 μm, Forsman Technology (Beijing) Co., Ltd.

[0031] Furthermore, the cross-linking agent is selected from chitosan solution.

[0032] Furthermore, the silicon precursor is selected from tetraethyl orthosilicate.

[0033] Furthermore, the composite adhesive is specifically prepared by the following steps:

[0034] B1. Add corn straw cellulose to 75-85% ethanol aqueous solution, stir at 60-70°C for 25-35 minutes, add sodium hydroxide, stir for 1-3 hours, add chloroacetic acid, stir for 1-2 hours, add 98.5-99.5% acetic acid to adjust the pH to 5-7, filter, wash and dry to obtain carboxymethyl cellulose;

[0035] B2. Mix the phosphoric acid aqueous solution and the ammonium aluminum sulfate aqueous solution, stir evenly, add carboxymethyl cellulose, continue stirring, and let stand to obtain a composite binder.

[0036] Furthermore, in the above-mentioned B1 reaction process, the ethanol aqueous solution is used as an organic solvent, and the sodium hydroxide can activate the hydroxyl groups on the surface of the corn straw cellulose, so that the chloroacetic acid can react with the hydroxyl groups on the surface of the corn straw cellulose to form carboxymethyl cellulose.

[0037] Furthermore, in the above-mentioned B2 reaction process, carboxymethyl cellulose, as a water-soluble high molecular polymer, has a long chain structure that can be dispersed in an aqueous phosphoric acid solution and an ammonium aluminum sulfate solution, and can significantly increase the viscosity of the acid solution and the ammonium aluminum sulfate solution, and improve the stability of the phosphoric acid solution and the ammonium aluminum sulfate solution.

[0038] Furthermore, in step B1, the ratio of the corn straw cellulose, ethanol aqueous solution, sodium hydroxide and chloroacetic acid is (1-1.4) g: (75-85) mL: (0.3-0.7) g: (0.2-0.4) g.

[0039] Furthermore, in step B2, the phosphoric acid aqueous solution, the ammonium aluminum sulfate aqueous solution, and the carboxymethyl cellulose are used in a ratio of (25-35) mL: (8-12) mL: (0.3-0.7) g.

[0040] Furthermore, the mass fraction of the phosphoric acid aqueous solution is 23-27%.

[0041] Furthermore, the mass fraction of the aqueous solution of ammonium aluminum sulfate is 12-14%.

[0042] Furthermore, the degree of substitution of the carboxymethyl cellulose is 1.05-1.09.

[0043] The present invention has the following beneficial effects:

[0044] (1) In the technical solution of the present invention, a polydopamine layer is formed on the surface of the silicon carbide whisker, which has high adhesion and can adsorb zirconium oxychloride and magnesium nitrate hexahydrate onto the surface of the pretreated silicon carbide whisker as a synthesis site for nano zirconium oxide and nano magnesium oxide. The silicon carbide whisker has an excellent aspect ratio and excellent fluidity. During the sintering process of the nano alumina ceramic, it can be filled into the pores of the nano alumina ceramic to improve the density and the mechanical strength of the nano alumina ceramic. Nano zirconium oxide and nano magnesium oxide are formed on the surface of the pretreated silicon carbide whisker. Nano zirconium oxide and nano magnesium oxide serve as sintering aids. During the sintering process, they can form a solid solution with nano alumina and fill in the space between nano alumina particles, thereby inhibiting the growth of nano alumina grains, promoting the elimination of pores, and enhancing the densification of alumina ceramics. The formed solid solution serves as a bridge between silicon carbide whiskers and nano alumina particles, significantly enhancing the bonding force of silicon carbide whiskers in the nano alumina ceramic matrix, avoiding the increase in porosity of the formed nano alumina ceramics due to the easy agglomeration of silicon carbide whiskers during the sintering process, thereby affecting the mechanical strength of the nano alumina ceramics.

[0045] (2) In the technical scheme of the present invention, the modified silicon carbide whiskers are embedded in the silica gel network structure to achieve the fixation of the modified silicon carbide whiskers by the composite gel, and further improve the dispersibility of the modified silicon carbide whiskers in the nano-alumina particles; the gel is filled into the nano-alumina particle system, and is molded and dried to form a green body. The silica gel serves as the skeleton of the nano-alumina green body and has a high compressive strength, so that the nano-alumina green body can be formed by pressing and can withstand the subsequent heating and cooling process of cracking and sintering without causing cracks in the body, thereby enhancing the stability of the nano-alumina ceramic product; during the sintering process of the silica gel, the organic matter in the gel is removed, and at the same time, the Si-O-Si bonds between the gels are further strengthened and cross-linked, which can form a denser silica network structure in the nano-alumina ceramic system, so that the nano-alumina particles are firmly bonded together through the silica network structure, and due to the formation of a dense silica network, it has high hardness and thermal stability, thereby enhancing the mechanical strength of the ceramic.

[0046] (3) In the technical scheme of the present invention, phosphoric acid solution, ammonium aluminum sulfate solution and carboxymethyl cellulose form a composite binder, which adheres to the surface of nano-alumina particles together with the composite gel. On the one hand, carboxymethyl cellulose, as a water-soluble high molecular polymer, can significantly increase the viscosity of the acid solution and the ammonium aluminum sulfate solution, and improve the stability of the phosphoric acid solution and the ammonium aluminum sulfate solution. On the other hand, the oxygen-containing functional groups contained in the carboxymethyl cellulose can be combined with the polar functional groups on the surface of the nano-alumina particles through chemical bonds, so that the carboxymethyl cellulose forms a film layer on the surface of the nano-alumina particles, and then the phosphoric acid and ammonium aluminum sulfate are firmly combined on the surface of the nano-alumina particles, avoiding the weak combination of phosphoric acid and ammonium aluminum sulfate with the nano-alumina particles, which affects the uniformity of the nano-alumina ceramics. In addition, the formed composite binder can also increase the bonding force between the composite gel and the nano-alumina particles. After molding and drying, the nano-alumina particles form a denser green body, which is beneficial to reduce the generation of pores in the nano-alumina ceramics during the sintering process, improve the density, and enhance the mechanical strength.

[0047] (4) In the technical solution of the present invention, during the sintering process, when the temperature reaches 900°C, the phosphoric acid in the composite binder can react with ammonium aluminum sulfate and nano-alumina. At 1200°C, a quartz-type aluminum phosphate layer can be formed on the surface of the nano-alumina particles. The formed quartz-type aluminum phosphate layer can also be used as a binder in the nano-alumina ceramics, making the nano-alumina ceramics denser during the sintering process. In addition, the quartz-type aluminum phosphate can also promote the sintering of the nano-alumina particles and enhance the strength of the nano-alumina ceramics. DETAILED DESCRIPTION

[0048] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.

[0050] Wherein, the alumina powder is selected from α-alumina, with a content of 99.5-99.8%, a particle size of 100-300nm, and industrial purity.

[0051] The degree of substitution of carboxymethyl cellulose is 1.05-1.09.

[0052] The diameter of silicon carbide whiskers is 80-100nm and the length is 0.2-1μm, Fosman Technology (Beijing) Co., Ltd.

[0053] Corn stalk cellulose is specifically prepared by the following steps:

[0054] The corn stalks were washed, dried and crushed, passed through a 60-mesh sieve to obtain stalk powder, 1 g of stalk powder was mixed with 20 mL of a 5% sodium hydroxide aqueous solution, stirred at 80 ° C for 2 h, filtered, washed, and the precipitate was collected. 1 g of the precipitate was added to a 0.25 mol / L sodium chlorite solution, the pH was adjusted to 6.5 with 10% hydrochloric acid, stirred at 75 ° C for 40 min, filtered, and washed three times with deionized water to obtain corn stalk cellulose.

[0055] Example 1

[0056] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0057] S1. Alumina powder, a composite binder, a composite gel, polyethylene glycol, and ethanol were mixed and added to a ball mill for ball milling for 20 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol was 90:8:10:1:25;

[0058] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 80 MPa, the pressing and drying temperature is 70 ° C, and the pressing and drying time is 25 min;

[0059] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 480°C at a heating rate of 1°C / min, and keep warm for 28 minutes; then continue to heat up to 980°C at a heating rate of 2°C / min, keep warm for 28 minutes, and finally heat up to 1480°C at a heating rate of 4°C / min, and keep warm for 2 hours.

[0060] The composite gel is specifically prepared by the following steps:

[0061] A1. Add 2 g of silicon carbide whiskers to 45 mL of Tris-HCl buffer at pH 8, stir evenly, add 0.3 g of dopamine, stir and react at 25 ° C for 24 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated silicon carbide whiskers;

[0062] A2. 5 g of pretreated silicon carbide whiskers, 1 g of zirconium oxychloride, and 1.2 g of magnesium nitrate hexahydrate were added to 45 mL of deionized water, stirred evenly, and a concentration of 4 mol / L of ammonia was added to adjust the pH to 8, stirred at 350 rpm for 25 min, filtered, dried in an oven at 90 ° C for 30 min, placed in a muffle furnace, calcined at 1200 ° C for 20 min, and cooled to room temperature to obtain modified silicon carbide whiskers;

[0063] A3. Mix 1 g of modified silicon carbide whisker with 15 mL of 1% chitosan solution, stir at 450 r / min for 1 h, add 0.3 g of tetraethyl orthosilicate and 8 mL of ethanol, stir until gelation, take out the gel, and wash it with deionized water three times to obtain a composite gel.

[0064] The composite adhesive is specifically prepared by the following steps:

[0065] B1. Add 1 g corn straw cellulose to 75 mL 75% ethanol aqueous solution, stir at 60°C for 25 min, add 0.3 g sodium hydroxide, stir for 1 h, add 0.2 g chloroacetic acid, stir for 1 h, add 98.5% acetic acid to adjust the pH to 5, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 8 min to obtain carboxymethyl cellulose;

[0066] B2. Mix 25 mL of 23% phosphoric acid aqueous solution and 8 mL of 12% aluminum ammonium sulfate aqueous solution, stir evenly, add 0.3 g of carboxymethyl cellulose, continue stirring for 20 min, and let stand for 10 min to obtain a composite adhesive.

[0067] Example 2

[0068] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0069] S1. Alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol were mixed and added to a ball mill for ball milling for 21 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol was 95:9:11:2:30;

[0070] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 90 MPa, the pressing and drying temperature is 80 ° C, and the pressing and drying time is 30 min;

[0071] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 500°C at a heating rate of 2°C / min, and keep warm for 30 minutes; then continue to heat up to 1000°C at a heating rate of 3°C / min, keep warm for 30 minutes, and finally heat up to 1500°C at a heating rate of 5°C / min, and keep warm for 3 hours.

[0072] The composite gel is specifically prepared by the following steps:

[0073] A1. Add 2.3 g of silicon carbide whiskers to 47 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.5 g of dopamine, stir to react, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated silicon carbide whiskers;

[0074] A2. 5.6 g of pretreated silicon carbide whiskers, 1.5 g of zirconium oxychloride, and 1.3 g of magnesium nitrate hexahydrate were added to 50 mL of deionized water, stirred evenly, and a concentration of 5 mol / L of ammonia was added to adjust the pH to 8.5, stirred at 400 rpm for 30 min, filtered, dried in an oven at 90 ° C for 30 min, placed in a muffle furnace, calcined at 1250 ° C for 22 min, and cooled to room temperature to obtain modified silicon carbide whiskers;

[0075] A3. Mix 1.5 g of modified silicon carbide whiskers with 20 mL of 2% chitosan solution, stir at 500 r / min for 2 h, add 0.3 g of tetraethyl orthosilicate and 10 mL of ethanol, stir until gelation, take out the gel, and wash it with deionized water three times to obtain a composite gel.

[0076] The composite adhesive is specifically prepared by the following steps:

[0077] B1. Add 1.2 g corn straw cellulose to 80 mL 80% ethanol aqueous solution, stir at 65°C for 35 min, add 0.5 g sodium hydroxide, stir for 2 h, add 0.3 g chloroacetic acid, stir for 1.5 h, add 99% acetic acid to adjust the pH to 6, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 8 min to obtain carboxymethyl cellulose;

[0078] B2. Mix 30 mL of 25% phosphoric acid aqueous solution and 10 mL of 13% aluminum ammonium sulfate aqueous solution, stir evenly, add 0.5 g of carboxymethyl cellulose, continue stirring for 20 min, and let stand for 10 min to obtain a composite adhesive.

[0079] Example 3

[0080] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0081] S1. Alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol were mixed and added to a ball mill for ball milling for 22 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol was 10010:12:3:35;

[0082] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 100 MPa, the pressing and drying temperature is 90 ° C, and the pressing and drying time is 35 min;

[0083] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 520°C at a heating rate of 3°C / min, and keep warm for 32 minutes; then continue to heat up to 1020°C at a heating rate of 4°C / min, keep warm for 32 minutes, and finally heat up to 1550°C at a heating rate of 6°C / min, and keep warm for 4 hours.

[0084] The composite gel is specifically prepared by the following steps:

[0085] A1. Add 2.5 g of silicon carbide whiskers to 50 mL of Tris-HCl buffer at pH 9, stir evenly, add 0.7 g of dopamine, stir to react, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated silicon carbide whiskers;

[0086] A2. 6 g of pretreated silicon carbide whiskers, 2 g of zirconium oxychloride, and 1.4 g of magnesium nitrate hexahydrate were added to 55 mL of deionized water, stirred evenly, and a concentration of 6 mol / L of ammonia was added to adjust the pH to 9, stirred at 450 rpm for 35 min, filtered, dried in an oven at 90 ° C for 30 min, placed in a muffle furnace, calcined at 1300 ° C for 23 min, and cooled to room temperature to obtain modified silicon carbide whiskers;

[0087] A3. Mix 2 g of modified silicon carbide whiskers with 25 mL of 3% chitosan solution, stir at 550 r / min for 3 h, add 0.7 g of tetraethyl orthosilicate and 12 mL of ethanol, stir until gelation, take out the gel, and wash it with deionized water three times to obtain a composite gel.

[0088] The composite adhesive is specifically prepared by the following steps:

[0089] B1. Add 1.4 g corn straw cellulose to 85 mL 85% ethanol aqueous solution, stir at 70°C for 35 min, add 0.7 g sodium hydroxide, stir for 3 h, add 0.4 g chloroacetic acid, stir for 2 h, add 99.5% acetic acid to adjust the pH to 7, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 8 min to obtain carboxymethyl cellulose;

[0090] B2. Mix 35 mL of 27% phosphoric acid aqueous solution and 12 mL of 14% aluminum ammonium sulfate aqueous solution, stir evenly, add 0.7 g of carboxymethyl cellulose, continue stirring for 20 min, and let stand for 10 min to obtain a composite adhesive.

[0091] Comparative Example 1

[0092] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0093] S1. Alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol were mixed and added to a ball mill for ball milling for 22 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol was 10010:12:3:35;

[0094] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 100 MPa, the pressing and drying temperature is 90 ° C, and the pressing and drying time is 35 min;

[0095] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 520°C at a heating rate of 3°C / min, and keep warm for 32 minutes; then continue to heat up to 1020°C at a heating rate of 4°C / min, keep warm for 32 minutes, and finally heat up to 1550°C at a heating rate of 6°C / min, and keep warm for 4 hours.

[0096] The composite gel is specifically prepared by the following steps:

[0097] A1. 6 g of silicon carbide whiskers, 2 g of zirconium oxychloride, and 1.4 g of magnesium nitrate hexahydrate were added to 55 mL of deionized water, stirred evenly, and ammonia water with a concentration of 6 mol / L was added to adjust the pH to 9. The mixture was stirred at 450 rpm for 35 min, filtered, dried in an oven at 90 ° C for 30 min, placed in a muffle furnace, calcined at 1300 ° C for 23 min, and cooled to room temperature to obtain modified silicon carbide whiskers;

[0098] A2. Mix 2 g of modified silicon carbide whiskers with 25 mL of 3% chitosan solution, stir at 550 r / min for 3 h, add 0.7 g of tetraethyl orthosilicate and 12 mL of ethanol, stir until gelation, take out the gel, and wash it with deionized water three times to obtain a composite gel.

[0099] The composite adhesive is specifically prepared by the following steps:

[0100] B1. Add 1.4 g corn straw cellulose to 85 mL 85% ethanol aqueous solution, stir at 70°C for 35 min, add 0.7 g sodium hydroxide, stir for 3 h, add 0.4 g chloroacetic acid, stir for 2 h, add 99.5% acetic acid to adjust the pH to 7, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 8 min to obtain carboxymethyl cellulose;

[0101] B2. Mix 35 mL of 27% phosphoric acid aqueous solution and 12 mL of 14% aluminum ammonium sulfate aqueous solution, stir evenly, add 0.7 g of carboxymethyl cellulose, continue stirring for 20 min, and let stand for 10 min to obtain a composite adhesive.

[0102] Comparative Example 2

[0103] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0104] S1. Alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol were mixed and added to a ball mill for ball milling for 22 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol was 10010:12:3:35;

[0105] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 100 MPa, the pressing and drying temperature is 90 ° C, and the pressing and drying time is 35 min;

[0106] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 520°C at a heating rate of 3°C / min, and keep warm for 32 minutes; then continue to heat up to 1020°C at a heating rate of 4°C / min, keep warm for 32 minutes, and finally heat up to 1550°C at a heating rate of 6°C / min, and keep warm for 4 hours.

[0107] The composite gel is specifically prepared by the following steps:

[0108] A1. Add 2.5 g of silicon carbide whiskers to 50 mL of Tris-HCl buffer at pH 9, stir evenly, add 0.7 g of dopamine, stir to react, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated silicon carbide whiskers;

[0109] A2. Mix 2 g of pretreated silicon carbide whiskers with 25 mL of 3% chitosan solution, stir at 550 r / min for 3 h, add 0.7 g of tetraethyl orthosilicate and 12 mL of ethanol, stir until gelation, take out the gel, and wash it with deionized water three times to obtain a composite gel.

[0110] The composite adhesive is specifically prepared by the following steps:

[0111] B1. Add 1.4 g corn straw cellulose to 85 mL 85% ethanol aqueous solution, stir at 70°C for 35 min, add 0.7 g sodium hydroxide, stir for 3 h, add 0.4 g chloroacetic acid, stir for 2 h, add 99.5% acetic acid to adjust the pH to 7, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 8 min to obtain carboxymethyl cellulose;

[0112] B2. Mix 35 mL of 27% phosphoric acid aqueous solution and 12 mL of 14% aluminum ammonium sulfate aqueous solution, stir evenly, add 0.7 g of carboxymethyl cellulose, continue stirring for 20 min, and let stand for 10 min to obtain a composite adhesive.

[0113] Comparative Example 3

[0114] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0115] S1. Alumina powder, a composite binder, modified silicon carbide whiskers, polyethylene glycol, and ethanol were mixed and added to a ball mill for ball milling for 22 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol was 10010:12:3:35;

[0116] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 100 MPa, the pressing and drying temperature is 90 ° C, and the pressing and drying time is 35 min;

[0117] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 520°C at a heating rate of 3°C / min, and keep warm for 32 minutes; then continue to heat up to 1020°C at a heating rate of 4°C / min, keep warm for 32 minutes, and finally heat up to 1550°C at a heating rate of 6°C / min, and keep warm for 4 hours.

[0118] The modified silicon carbide whiskers are specifically prepared by the following steps:

[0119] A1. Add 2.5 g of silicon carbide whiskers to 50 mL of Tris-HCl buffer at pH 9, stir evenly, add 0.7 g of dopamine, stir to react, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated silicon carbide whiskers;

[0120] A2. Add 6 g of pretreated silicon carbide whiskers, 2 g of zirconium oxychloride, and 1.4 g of magnesium nitrate hexahydrate to 55 mL of deionized water, stir evenly, add 6 mol / L ammonia water to adjust the pH to 9, stir at 450 rpm for 35 min, filter, dry in an oven at 90 ° C for 30 min, place in a muffle furnace, calcine at 1300 ° C for 23 min, and cool to room temperature to obtain modified silicon carbide whiskers.

[0121] The composite adhesive is specifically prepared by the following steps:

[0122] B1. Add 1.4 g corn straw cellulose to 85 mL 85% ethanol aqueous solution, stir at 70°C for 35 min, add 0.7 g sodium hydroxide, stir for 3 h, add 0.4 g chloroacetic acid, stir for 2 h, add 99.5% acetic acid to adjust the pH to 7, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 8 min to obtain carboxymethyl cellulose;

[0123] B2. Mix 35 mL of 27% phosphoric acid aqueous solution and 12 mL of 14% aluminum ammonium sulfate aqueous solution, stir evenly, add 0.7 g of carboxymethyl cellulose, continue stirring for 20 min, and let stand for 10 min to obtain a composite adhesive.

[0124] Comparative Example 4

[0125] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0126] S1. The alumina powder, composite gel, polyethylene glycol and ethanol were mixed and added to a ball mill for ball milling for 22 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol and ethanol was 10010:12:3:35;

[0127] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 100 MPa, the pressing and drying temperature is 90 ° C, and the pressing and drying time is 35 min;

[0128] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 520°C at a heating rate of 3°C / min, and keep warm for 32 minutes; then continue to heat up to 1020°C at a heating rate of 4°C / min, keep warm for 32 minutes, and finally heat up to 1550°C at a heating rate of 6°C / min, and keep warm for 4 hours.

[0129] The composite gel is specifically prepared by the following steps:

[0130] A1. Add 2.5 g of silicon carbide whiskers to 50 mL of Tris-HCl buffer at pH 9, stir evenly, add 0.7 g of dopamine, stir to react, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated silicon carbide whiskers;

[0131] A2. 6 g of pretreated silicon carbide whiskers, 2 g of zirconium oxychloride, and 1.4 g of magnesium nitrate hexahydrate were added to 55 mL of deionized water, stirred evenly, and a concentration of 6 mol / L of ammonia was added to adjust the pH to 9, stirred at 450 rpm for 35 min, filtered, dried in an oven at 90 ° C for 30 min, placed in a muffle furnace, calcined at 1300 ° C for 23 min, and cooled to room temperature to obtain modified silicon carbide whiskers;

[0132] A3. Mix 2 g of modified silicon carbide whiskers with 25 mL of 3% chitosan solution, stir at 550 r / min for 3 h, add 0.7 g of tetraethyl orthosilicate and 12 mL of ethanol, stir until gelation, take out the gel, and wash it with deionized water three times to obtain a composite gel.

[0133] The composite adhesive is specifically prepared by the following steps:

[0134] 35 mL of 27% by mass phosphoric acid aqueous solution and 12 mL of 14% by mass aluminum ammonium sulfate aqueous solution were mixed and stirred evenly, 0.7 g of corn straw cellulose was added, stirring was continued for 20 minutes, and the mixture was allowed to stand for 10 minutes to obtain a composite binder.

[0135] Comparative Example 5

[0136] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0137] S1. Alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol were mixed and added to a ball mill for ball milling for 22 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol was 10010:12:3:35;

[0138] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 100 MPa, the pressing and drying temperature is 90 ° C, and the pressing and drying time is 35 min;

[0139] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 520°C at a heating rate of 3°C / min, and keep warm for 32 minutes; then continue to heat up to 1020°C at a heating rate of 4°C / min, keep warm for 32 minutes, and finally heat up to 1550°C at a heating rate of 6°C / min, and keep warm for 4 hours.

[0140] The composite gel is specifically prepared by the following steps:

[0141] A1. Add 2.5 g of silicon carbide whiskers to 50 mL of Tris-HCl buffer at pH 9, stir evenly, add 0.7 g of dopamine, stir to react, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated silicon carbide whiskers;

[0142] A2. 6 g of pretreated silicon carbide whiskers, 2 g of zirconium oxychloride, and 1.4 g of magnesium nitrate hexahydrate were added to 55 mL of deionized water, stirred evenly, and a concentration of 6 mol / L of ammonia was added to adjust the pH to 9, stirred at 450 rpm for 35 min, filtered, dried in an oven at 90 ° C for 30 min, placed in a muffle furnace, calcined at 1300 ° C for 23 min, and cooled to room temperature to obtain modified silicon carbide whiskers;

[0143] A3. Mix 2 g of modified silicon carbide whiskers with 25 mL of 3% chitosan solution, stir at 550 r / min for 3 h, add 0.7 g of tetraethyl orthosilicate and 12 mL of ethanol, stir until gelation, take out the gel, and wash it with deionized water three times to obtain a composite gel.

[0144] The composite adhesive is specifically prepared by the following steps:

[0145] B1. Add 1.4 g corn straw cellulose to 85 mL 85% ethanol aqueous solution, stir at 70°C for 35 min, add 0.7 g sodium hydroxide, stir for 3 h, add 0.4 g chloroacetic acid, stir for 2 h, add 99.5% acetic acid to adjust the pH to 7, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 8 min to obtain carboxymethyl cellulose;

[0146] B2. Mix 12 mL of 14% ammonium aluminum sulfate aqueous solution and 0.7 g of carboxymethyl cellulose, stir for 20 min, and let stand for 10 min to obtain a composite binder.

[0147] Comparative Example 6

[0148] A preparation process of a high-strength nano-alumina ceramic product comprises the following preparation steps:

[0149] S1. Alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol were mixed and added to a ball mill for ball milling for 22 hours to obtain a composite slurry, wherein the mass ratio of alumina powder, composite binder, composite gel, polyethylene glycol, and ethanol was 10010:12:3:35;

[0150] S2. The composite slurry is placed in a mold having a size of 40 mm × 40 mm × 50 mm, and is pressed and dried to obtain a green body, wherein the pressing and drying pressure is 100 MPa, the pressing and drying temperature is 90 ° C, and the pressing and drying time is 35 min;

[0151] S3. Place the green body in a high-temperature sintering furnace for high-temperature sintering, and then cool to room temperature to obtain a nano-alumina ceramic product, wherein the high-temperature sintering process: heat up to 520°C at a heating rate of 3°C / min, and keep warm for 32 minutes; then continue to heat up to 1020°C at a heating rate of 4°C / min, keep warm for 32 minutes, and finally heat up to 1550°C at a heating rate of 6°C / min, and keep warm for 4 hours.

[0152] The composite gel is specifically prepared by the following steps:

[0153] A1. Add 2.5 g of silicon carbide whiskers to 50 mL of Tris-HCl buffer at pH 9, stir evenly, add 0.7 g of dopamine, stir to react, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain pretreated silicon carbide whiskers;

[0154] A2. 6 g of pretreated silicon carbide whiskers, 2 g of zirconium oxychloride, and 1.4 g of magnesium nitrate hexahydrate were added to 55 mL of deionized water, stirred evenly, and a concentration of 6 mol / L of ammonia was added to adjust the pH to 9, stirred at 450 rpm for 35 min, filtered, dried in an oven at 90 ° C for 30 min, placed in a muffle furnace, calcined at 1300 ° C for 23 min, and cooled to room temperature to obtain modified silicon carbide whiskers;

[0155] A3. Mix 2 g of modified silicon carbide whiskers with 25 mL of 3% chitosan solution, stir at 550 r / min for 3 h, add 0.7 g of tetraethyl orthosilicate and 12 mL of ethanol, stir until gelation, take out the gel, and wash it with deionized water three times to obtain a composite gel.

[0156] The composite adhesive is specifically prepared by the following steps:

[0157] B1. Add 1.4 g corn straw cellulose to 85 mL 85% ethanol aqueous solution, stir at 70°C for 35 min, add 0.7 g sodium hydroxide, stir for 3 h, add 0.4 g chloroacetic acid, stir for 2 h, add 99.5% acetic acid to adjust the pH to 7, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 8 min to obtain carboxymethyl cellulose;

[0158] B2. Mix 35 mL of 27% phosphoric acid aqueous solution and 0.7 g of carboxymethyl cellulose, stir for 20 min, and let stand for 10 min to obtain a composite adhesive.

[0159] The performance of the nano-alumina ceramic products prepared in Examples 1-3 and Comparative Examples 1-6 is now tested.

[0160] Porosity detection: FE-SEM instrument was used to take pictures of the nano-alumina ceramic products prepared above, and the porosity of the nano-alumina ceramic products was analyzed and calculated.

[0161] Density detection: The density of the nano-alumina ceramic product prepared above was detected using an ET-120HM density meter and the Archimedes drainage method.

[0162] Rockwell hardness test: A Rockwell hardness tester was used to test the Rockwell hardness of the nano-alumina ceramic product prepared above.

[0163] Compressive strength test: The compressive strength of the nano-alumina ceramic product prepared above is tested according to GB / T4740-1999 “Test method for compressive strength of ceramic materials”.

[0164] Fracture toughness test: According to GB / T23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method", the fracture toughness value of the nano-alumina ceramic product prepared above was tested. As shown in Table 1 below.

[0165] Table 1 Performance test of nano-alumina ceramic products prepared in Examples 1-3 and Comparative Examples 1-6

[0166]

[0167] It can be seen from the data in Table 1 that the nano-alumina ceramic products prepared in Examples 1-3 have high density, mechanical strength and uniformity. In Comparative Example 1, the pre-treated silicon carbide whiskers were replaced with a composite gel prepared from silicon carbide whiskers and added to the nano-alumina ceramic products, and the mechanical strength and density thereof decreased, proving that a polydopamine layer was formed on the surface of the silicon carbide whiskers as a synthesis site for nano-zirconium oxide and nano-magnesium oxide, and the solid solution formed by nano-zirconium oxide and nano-magnesium oxide and nano-alumina served as a bridge between silicon carbide whiskers and nano-alumina particles, significantly enhancing the binding force of silicon carbide whiskers in the nano-alumina ceramic matrix and preventing the silicon carbide whiskers from agglomerating easily.

[0168] In Comparative Example 2, the modified silicon carbide whiskers were replaced with a composite gel prepared by pretreated silicon carbide whiskers and added to the nano-alumina ceramic product. The mechanical strength and density of the product decreased, proving that nano-zirconium oxide and nano-magnesium oxide were formed on the surface of the pretreated silicon carbide whiskers. The formed nano-zirconium oxide and nano-magnesium oxide acted as sintering aids. During the sintering process, they could form a solid solution with nano-alumina and fill in the spaces between the nano-alumina particles, thereby inhibiting the growth of the nano-alumina grains and promoting the removal of pores.

[0169] In Comparative Example 3, the composite gel is replaced with modified silicon carbide whiskers and added to the nano-alumina ceramic product. The mechanical strength and density of the product decrease, indicating that the modified silicon carbide whiskers are embedded in the silica gel network structure. The silica gel serves as the nano-alumina green body skeleton and can withstand the subsequent heating and cooling processes of pyrolysis and sintering without causing cracks in the body, thereby enhancing the stability of the nano-alumina ceramic product. The Si-O-Si bonds between the gels are further strengthened and cross-linked, giving the product high hardness and thermal stability, thereby enhancing the mechanical strength of the ceramic.

[0170] In Comparative Example 4, carboxymethyl cellulose was replaced with a composite binder prepared from corn straw cellulose and added to the nano-alumina ceramic product. The mechanical strength and density of the product decreased, proving that the oxygen-containing functional groups contained in the carboxymethyl cellulose can be chemically bonded to the polar functional groups on the surface of the nano-alumina particles, so that the carboxymethyl cellulose forms a film layer on the surface of the nano-alumina particles, and then firmly binds the phosphate and ammonium aluminum sulfate to the surface of the nano-alumina particles, thereby improving the dispersibility of the nano-alumina particles.

[0171] The composite binder prepared without adding aqueous phosphoric acid solution and ammonium aluminum sulfate solution in Comparative Examples 5 and 6 was added to the nano-alumina ceramic products, and its mechanical strength and density decreased, proving that during the sintering process, phosphoric acid can react with ammonium aluminum sulfate and nano-alumina to form a quartz-type aluminum phosphate layer on the surface of the nano-alumina particles. Quartz-type aluminum phosphate can also promote the sintering of nano-alumina particles and enhance the strength of nano-alumina ceramics.

[0172] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0173] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A preparation process of a high-strength nano-alumina ceramic product, characterized in that: The method comprises the following preparation steps: S1. The alumina powder, composite binder, composite gel, plasticizer, and solvent were mixed and ball-milled for 20-22h to obtain a composite slurry; S2. The composite slurry is placed in a mold, molded and dried to obtain a green body; S3. The green body is placed in a high temperature sintering furnace, sintered at high temperature, and then cooled to room temperature to obtain a nano-alumina ceramic product; The composite gel is obtained by mixing and reacting modified silicon carbide whiskers, a crosslinking agent and a silicon precursor; The modified silicon carbide whisker is obtained by mixing pretreated silicon carbide whisker, zirconium oxychloride and magnesium nitrate hexahydrate and calcining at high temperature; The composite gel is specifically prepared by the following steps: A1. Add silicon carbide whiskers to a Tris-HCl buffer having a pH of 8-9, stir evenly, add dopamine, stir the reaction, filter, wash, and dry to obtain pretreated silicon carbide whiskers; A2. The pretreated silicon carbide whiskers, zirconium oxychloride, and magnesium nitrate hexahydrate were added to deionized water, stirred evenly, and ammonia water with a concentration of 4-6 mol / L was added to adjust the pH to 8-9, stirred at a rate of 350-450 rpm for 25-35 min, filtered, dried, placed in a muffle furnace, calcined at 1200-1300 ° C for 20-23 min, and cooled to room temperature to obtain modified silicon carbide whiskers; A3. The modified silicon carbide whiskers were mixed with a crosslinking agent having a mass fraction of 1-3%, stirred at a rate of 450-550 r / min for 1-3 h, a silicon precursor and ethanol were added, stirred until gelation occurred, the gel was removed, and washed to obtain a composite gel; The composite binder is obtained by mixing a phosphoric acid aqueous solution, an ammonium aluminum sulfate aqueous solution, and carboxymethyl cellulose; The composite binder is specifically prepared by the following steps: B1. Add corn straw cellulose to 75-85% ethanol aqueous solution, stir at 60-70°C for 25-35 minutes, add sodium hydroxide, stir for 1-3 hours, add chloroacetic acid, stir for 1-2 hours, add 98.5-99.5% acetic acid to adjust the pH to 5-7, filter, wash and dry to obtain carboxymethyl cellulose; B2. Mix the phosphoric acid aqueous solution and the ammonium aluminum sulfate aqueous solution, stir evenly, add carboxymethyl cellulose, continue stirring, and let stand to obtain a composite binder.

2. The preparation process of a high-strength nano-alumina ceramic product according to claim 1, characterized in that: In step A1, the amount ratio of the silicon carbide whisker, Tris-HCl buffer, and dopamine is (2-2.5) g: (45-50) mL: (0.6-1) g.

3. The preparation process of a high-strength nano-alumina ceramic product according to claim 1, characterized in that: In step A2, the ratio of the pretreated silicon carbide whisker, zirconium oxychloride, magnesium nitrate hexahydrate, and deionized water is (5-6) g: (1-2) g: (1.2-1.4) g: (45-55) mL.

4. The preparation process of a high-strength nano-alumina ceramic product according to claim 1, characterized in that: In step A3, the amount ratio of the modified silicon carbide whisker, the crosslinking agent, the silicon precursor, and the ethanol is (1-2) g: (15-25) mL: (0.3-0.7) g: (8-12) mL.

5. The preparation process of a high-strength nano-alumina ceramic product according to claim 1, characterized in that: In step B1, the amount ratio of corn straw cellulose, ethanol aqueous solution, sodium hydroxide, and chloroacetic acid is (1-1.4) g: (75-85) mL: (0.3-0.7) g: (0.2-0.4) g; in step B2, the amount ratio of phosphoric acid aqueous solution, ammonium aluminum sulfate aqueous solution, and carboxymethyl cellulose is (25-35) mL: (8-12) mL: (0.3-0.7) g.

6. The preparation process of a high-strength nano-alumina ceramic product according to claim 1, characterized in that: The mass fraction of the phosphoric acid aqueous solution is 23-27%; the mass fraction of the ammonium aluminum sulfate aqueous solution is 12-14%.

7. The preparation process of a high-strength nano-alumina ceramic product according to claim 1, characterized in that: The alumina powder is selected from α-alumina, with a content of 99.5-99.8% and a particle size of 100-300nm; the plasticizer is selected from polyethylene glycol; and the solvent is selected from ethanol.

8. A nano-alumina ceramic product obtained by the preparation process according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Aluminum oxide-based wear-resisting cutting ceramic and preparation method thereof

    CN104387039A

  • Foam silicon carbide ceramic and preparation and application thereof

    CN118908744A